169: A Detailed Examination of Infant Mortality Rates in Canada and Selected High Income Countries. Issue 6 (1st June 2014) - Deb-Rinker, P; Leon, JA; Gilbert, NL; Rouleau, J; Shah, PS; Sauve, R; Kramer, M; Joseph, KS
Abstract: BACKGROUND: Infant mortality rate is a key perinatal health indicator, widely used as an index of population health status. International comparisons of infant mortality rates need to be interpreted with caution. Differences in birth registration criteria are a recognised problem, especially for preterm infants at the borderline of viability. Variations in the reporting of stillbirths/live births are another concern. Varied definitions are used to calculate perinatal mortality rates and this is further complicated by whether induced abortions and terminations of pregnancy are included or excluded. OBJECTIVES: We examined perinatal and infant mortality rates in selected high income countries for evidence of differences in registration practices, classification of stillbirths and live births and selective registration of extremely preterm infants who survive. DESIGN/METHODS: We carried out a retrospective population-based cohort study using national data from Canada, the United States, Denmark, Finland, Iceland, Norway, and Sweden for the period 1995 to 2005. The main outcome measures included live birth distribution by gestational age and birth weight; gestational age- and birth weight-specific fetal, neonatal, and post-neonatal mortality; and cause-specific (congenital anomalies, immaturity-related and other conditions) infant mortality. RESULTS: Our results show country-specific live birth distributions by birth weight and gestational age, birth weight- and gestational age-specific mortality and cause-specific mortality over a 11 year period, from 1995 to 2005. We observed differences between countries when crude neonatal mortality rates were compared to neonatal mortality excluding near-viable births. Similar results were obtained for stillbirths but not for postneonatal mortality which were essentially unaffected by the exclusion of near-viable births. CONCLUSIONS: These findings provide a comprehensive perspective of infant mortality rates in these countries by using specific birth weight and gestational age cut-off values, to preclude artefacts that often arise from such international comparisons. It also highlights the need for standardizing birth registration and infant death registration procedures globally, in order for international comparisons of fetal and infant mortality rates to be more meaningful.